Trombocytosis in childhood relapsing nephrotic syndrome - Ade Hafni; Danny Hilmanto; Dedi Rachmadi; Nanan Sekarwana (Indonesian Pediatric Society, 2007)
Background Thrombosis is a serious complication of nephroticsyndrome (NS). Long-term steroid treatment may inducethrombocytosis in relapsing NS that may predispose to thrombosis.Most children with idiopathic NS respond to steroids; however, asubstantial number of patients will relapse frequently and requirerepeated high dose steroid therapy, thus increase the risk ofthrombocytosis.Objective To compare the occurrence of thrombocytosis betweenchildren with frequent relapses of NS (FRNS) and those withinfrequent relapses (IFRNS).Methods We reviewed the medical records of children aged 1-14years diagnosed as FRNS and IFRNS at the Department of ChildHealth, Hasan Sadikin General Hospital Bandung from 2000-2005. We excluded children with iron deficiency anemia,hemolytic anemia, acute haemorrhage, malignancy, and those whoreceived cyclophosphamide.Results There were 33 children (26 males, 7 females) with FRNSand 33 children (27 males, 6 females) with IFRNS. The meanplatelet level of children with FRNS (517,909+165,670/ml) washigher than that of children with IFRNS (416,272+145,763/ml)(P=0.005). The occurrence of thrombocytosis in children withFRNS (18) was higher than that of children with IFRNS (7)(P=0.005).Conclusion This study shows that thrombocytosis is morecommon in FRNS than IFRNS, therefore we should take moreprecaution to the occurrence of thrombosis in FRNS.